Cold snare polypectomy of colorectal polyps ≤ 10 mm on clopidogrel: Australian and New Zealand randomized controlled trial - Ket, Shara; Tjandra, Douglas; Hewett, David G.; Kheir, Ammar O.; Metz, Andrew J.; Moss, Alan; Ogra, Ravinder; Tam, William; Raftopoulos, Spiro; Reynolds, John; Secomb, Robyn; Cavalieri, Lauren; Urquhart, Paul; Gibson, Peter R.; Brown, Gregor (Endoscopy International Open, 2022)
Background and study aims Optimal peri-colonoscopic management of clopidogrel remains unclear. Cold snare polypectomy is safe and effective for removing polyps ≤ 10 mm and clips can control intraprocedural bleeding. We conducted a randomized controlled trial to compare continuation of clopidogrel versus temporary replacement of clopidogrel with aspirin for routine colonoscopy using cold snare polypectomy for polyps ≤ 10 mm. Patients and methods Between August 2016 and August 2019, consenting participants at 12 centers were randomized to continuation of clopidogrel as a single or dual antiplatelet agent, or to temporarily take aspirin alone from 7 days prior to 2 days after routine colonoscopy. Endoscopists were blinded to group allocation. Cold snare polypectomy was used to remove polyps ≤ 10 mm, with endoscopic clips applied if intraprocedural bleeding continued for > 2 minutes. Follow-up was performed on Day 30. The trial was stopped early due to delayed patient enrollment.Results Two hundred seventy-six consecutive polyps ≤ 10 mm were removed from 107 patients. Of the patients, 61.7 % were male with a median age of 69 years (interquartile range [IQR] 63 to 76.75). Fifty-nine patients continued on clopidogrel and 48 temporarily took aspirin instead. One hundred thirty-four polyps were removed from 49 patients who continued on clopidogrel vs 142 from 43 patients temporarily took aspirin instead (P = 0.33). Intraprocedural bleeding requiring clips occurred in 11 of 49 patients who continued on clopidogrel and in two of 43 patients who temporarily took replacing with aspirin instead (P = 0.02). More post-procedural minor bleeding was seen in the aspirin arm (six of 43 vs one of 49; P = 0.03). One patient in each arm had acute coronary syndrome, which was medically managed. None of the patients had clinically significant post-procedural bleeding.Conclusions Continuation of clopidogrel in patients undergoing cold snare polypectomy for colorectal polyps ≤ 10 mm does not appear to increase the rate of clinically significant postpolypectomy bleeding. It is associated with an increase in intraprocedural bleeding, which can be successfully treated with clips.